2010
DOI: 10.1007/s12157-010-0213-7
|View full text |Cite
|
Sign up to set email alerts
|

Hépatite C chronique: épidémiologie, diagnostic et traitement au CHU Yalgado-Ouédraogo de Ouagadougou

Abstract: Notre travail a pour but d'étudier les aspects épidé-miologique, diagnostique et thérapeutique de l'hépatite C chronique. Patients et méthodes : Il s'agit d'une étude clinique prospective réalisée, d'octobre 2005 à décembre 2009, dans le service d'hépatogastroentérologie. Ont été inclus les patients anti-virus de l'hépatite C (VHC) et ARN-VHC positifs. La quantification de l'ARN-VHC a été réalisée par PCR en temps réel. Les malades ont été traités par la combinaison interféron pégylé alfa-2a et ribavirine.Résu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7]. HCV Japanese patients had an average age of 55 years [14].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…They were 42.3 years old for VHB which is consistent with other studies carried out in Côte d'Ivoire that found an average age of 42 years for chronic carriers of HBs Ag [9] and 40 [10], in France HBV patients had a median age of 44 years [11]. Our HCV patients were on average 51.9 years old, in line with SOMBIE et al who found an average age of 51 ± 6.9 years in HCV patients put on treatment [6] and a study in Morocco where HCV patients were on average 52 years old [12], in Tunisia the average age of HCV patients was 50 years [13] and 53.1 ± 8.1 years in Cameroon [7]. HCV Japanese patients had an average age of 55 years [14].…”
Section: Discussionsupporting
confidence: 92%
“…Our sex ratio was 1.56. Which is higher than HCV patients in Burkina Faso 1.25 [6] and in Tunisia whose patients had a sex ratio of 1.04 [13] but is consistent with Japanese patients who had a sex ratio of 1.57 [14].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Kowo et al [8] in 2018 in Cameroon had found a mean age close to ours (44.24±8.22 years). Sombié et al [9] in Burkina Faso in 2011 also found a mean age of 47 years. The young age of patients in these sub-Saharan studies could be explained by risky procedures such as scarification.…”
Section: Discussionmentioning
confidence: 90%